Experimental infection of cows with newly isolated Akabane virus strain (AKAV-7) causing encephalomyelitis. (December 2016) - Lee, Hyeyeoun; Jeong, Hansol; Park, Surim; Yang, Myeon-Sik; Kim, Jongwon; Bae, Jaehyun; Kwon, Yonghwan; Kim, Min-Su; Oem, Jae-Ku; Lee, Myoung-Heon; Lim, Chae-Woong; Kim, Bumseok
Abstract Akabane virus (AKAV), an arthropod-transmitted bunyavirus, is a major cause of congenital abnormalities and encephalomyelitis in ruminants. In 2010, there was a major outbreak of encephalomyelitis in Korea and fifteen AKAV strains, including AKAV-7, were isolated from cows. To identify the neuropathogenicity of AKAV-7, we performed experimental infection of cows. Six-month-old female Korean Holstein dairy cattle were inoculated with AKAV-7 by various routes, including intracerebral (IC), intrasubarachnoid space (IS), subcutaneous (SC) and intravenous (IV); a separate group was vaccinated before intravenous infection. Five of the six cows in the IC group and two of the six cows in the IS group showed clinical signs such as locomotor ataxia and paralysis of the hind limbs. Three of six cows died after IC infection 9–12 days post infection (dpi). Histopathologic changes such as nonsuppurative encephalomyelitis were confirmed in various parts of the central nervous system in the IC, IS and SC groups. Early onset of neutralizing antibodies in the serum and lower viral mRNA levels in the peripheral blood mononuclear cells (PBMCs) and various tissues in the vaccinated group was noticeable compared to the unvaccinated group (IV group). We suggest that the AKAV vaccine currently used in Korea may be partially effective for protection against AKAV-7 in cows.